Pengaruh Corporate Social Responsibility Terhadap Profitabilitas Perusahaan(Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Puspitasari, Rosi Denovi, Dr. Syamsudin, M.M (2017)
The purpose of this research is to know the influence of corporate social responsibility (CSR) using indicators of environmental, societal, and employment against the profitability of the company as measured by return on assets (ROA) annual reports on the manufacturing company. The population in this research is the manufacturing companies listed on the Indonesia stock exchange (idx) during the period 2013-2015 with sampling techniques using a purposive sampling method. Data obtained from the Indonesian Capital Market Directory (ICMD) and the Annual Report of a manufacturing company that lists and doing Corporate Social Responsibility during the years 2013 to 2015 are listed on the Indonesia stock exchange. Methods of data analysis used in this study was multiple linear regression. The results of this study indicate that during the period 2013-2015 environmental indicators have a positive and significant influence against the return on asset (ROA) for 0.003, societal indicators do not have positive and significant influence against the return on assets (ROA) of 0.260, and employment indicators have no positive influence and significantly to the return on assets (ROA) of 0.265. However, simultaneously the environmental indicators, employment, and community has a positive influence and significantly to the return on asset (ROA). Further research is expected to be able to add other independent variables of indicator in its effect on the dependent variable and retrieve the object wider research include other sectors.